Sex is a moderator of the association between NOS1AP sequence variants and QTc in two long QT syndrome founder populations: a pedigree-based measured genotype association analysis - Annika Winbo; Eva-Lena Stattin; Ida Maria Westin; Anna Norberg; Johan Persson; Steen M. Jensen; Annika Rydberg (BMC, 2017)
Abstract Background Sequence variants in the NOS1AP gene have repeatedly been reported to influence QTc, albeit with moderate effect sizes. In the long QT syndrome (LQTS), this may contribute to the substantial QTc variance seen among carriers of identical pathogenic sequence variants. Here we assess three non-coding NOS1AP sequence variants, chosen for their previously reported strong association with QTc in normal and LQTS populations, for association with QTc in two Swedish LQT1 founder populations. Methods This study included 312 individuals (58% females) from two LQT1 founder populations, whereof 227 genotype positive segregating either Y111C (n = 148) or R518* (n = 79) pathogenic sequence variants in the KCNQ1 gene, and 85 genotype negatives. All were genotyped for NOS1AP sequence variants rs12143842, rs16847548 and rs4657139, and tested for association with QTc length (effect size presented as mean difference between derived and wildtype, in ms), using a pedigree-based measured genotype association analysis. Mean QTc was obtained by repeated manual measurement (preferably in lead II) by one observer using coded 50 mm/s standard 12-lead ECGs. Results A substantial variance in mean QTc was seen in genotype positives 476 ± 36 ms (Y111C 483 ± 34 ms; R518* 462 ± 34 ms) and genotype negatives 433 ± 24 ms. Female sex was significantly associated with QTc prolongation in all genotype groups (p < 0.001). In a multivariable analysis including the entire study population and adjusted for KCNQ1 genotype, sex and age, NOS1AP sequence variants rs12143842 and rs16847548 (but not rs4657139) were significantly associated with QT prolongation, +18 ms (p = 0.0007) and +17 ms (p = 0.006), respectively. Significant sex-interactions were detected for both sequent variants (interaction term r = 0.892, p < 0.001 and r = 0.944, p < 0.001, respectively). Notably, across the genotype groups, when stratified by sex neither rs12143842 nor rs16847548 were significantly associated with QTc in females (both p = 0.16) while in males, a prolongation of +19 ms and +8 ms (p = 0.002 and p = 0.02) was seen in multivariable analysis, explaining up to 23% of QTc variance in all males. Conclusions Sex was identified as a moderator of the association between NOS1AP sequence variants and QTc in two LQT1 founder populations. This finding may contribute to QTc sex differences and affect the usefulness of NOS1AP as a marker for clinical risk stratification in LQTS.